India’s rural employment guarantee boosts demand for agricultural technology - Bhargava, Anil K.; International Maize and Wheat Improvement Center; International Food Policy Research Institute; International Livestock Research Institute; International Rice Research Institute; WorldFish (International Food Policy Research Institute, 2014)
This study shows that the program (i.e., MGNREGA) leads small and marginal farm owners to adopt labor-saving technologies that replace labor-intensive alternatives. In other words, MGNREGA decreases the threshold farm size associated with basic labor-saving technology use. In addition, MGNREGA’s focus on providing public water infrastructure appears to be decreasing the use of diesel and electric-powered water pumps. A focus on education and agricultural skill development may augment the chances that workers are prepared for a higher-productivity agricultural sector. Future data on long-run labor use, wages, output and technology adoption patterns will give much better insight into where MGNREGA villages end up in the long run.